217k views
11 votes
Solve this equation.
-4 (y - 3) = 36

2 Answers

1 vote

-4y + 12 = 36

-4y = 24

y = - 6

User Eigenchris
by
5.1k points
10 votes

Answer:

y = -6

Explanation:

To solve for y, you must isolate the variable by first dividing both sides by -4:

-4 (y-3) = 36

÷-4

y-3 = -9

Next, add 3 to both sides and you will get your final answer:

y-3 = -9

+3

y = -6

To check your answer, you can plug in -6 for y to ensure that the overall result is 36:

-4(-6-3) = -4(-9) = 36

36 = 36

Hope this helped!

User SaloGala
by
5.5k points